s Uma sequência didática para estimular o mecanismo atencional top-down em tarefas sobre as transformações trigonométricas que auxiliam no cálculo de limites - Oliveira, Geane Santana (2023)
The present research aims to propose a Didactic Sequence containing minimum requirements to stimulate top-down attentional mechanisms in students during tasks that explore trigonometric transformations, The choice of this subject of knowledge become evident when observe that there are no studies in the field of Mathematics Education regarding this topic, The methodological path of this research is based on the four pillars (phases) of Classical Didactic Engineering - CDE (preliminary analyses, conceptions and a priori analysis. Experimentation. a posteriori analysis. and validation). with Artigue (1988) being the pioneering scholar in this methodology in the field of Mathematics Didactics. through which the 1st and 2nd phases of this research methodology are execute, In the 1st phase of CDE. a historical. Epistemological. and customary teaching analysis is develope to understand the context (emergence and evolution) and the obstacles related to knowledge about the subject of study, The theoretical foundation of this research is anchored in the history of mathematics. (re)visiting Eves (2004) and Boyer (1996). in addition to the association with the theory of cognitive neuroscience. mainly seeking support from Gazzaniga et al. (2006). Sternberg (2010). Cosenza and Guerra (2011). Kandel (2014). with an emphasis on activating the top-down attentional mechanism to create a reference matrix for analyzing the tasks proposed in the high school textbook (Souza, 2021), Furthermore. to elaborate the Didactic Sequence. divided into six moments. the reference framework of Duval (2003). Chevallard (1998). and the theory of Cognitive Neuroscience that underpin the creation of the reference matrix for minimum requirements that would trigger the top-down attentional mechanism are use. and it is validate by members of neuroMATH (Research Group on Neurocognitive Development of Mathematical Learning at the Federal Institute of Sergipe), It is worth noting that the tasks is plan to meet the requirements that trigger the top-down attentional mechanism. with the possibility of making conversions between different ostensive objects by invoking non-ostensive technologies.